Neural Distributed Representations of Vector Data in Intelligent Information Technologies - Gritsenko, V.I.; Rachkovskij, D.A.; Revunova, E.G. (Кибернетика и вычислительная техника, 2018)
The purpose of the article is to provide an overview of a part of the work of the Department of Neural Information Processing Technologies (International Center) in the field of neural network distributed representations. The approach is a development of the ideas of Nikolai Mikhailovich Amosov and his scientific school of modeling the structure and functions of the brain.